Children’s poetry at Haitham Yahya Al-Khawaja - Al-Hmoudi, Suad Abdullah Rashid; Al-Qudah, Mohamed Ahmad; Darabsah, Mahmoud Mohamed (Al-Adab Journal, 2022)
This study tackles the efforts of the writer/ Haitham Yahya Al-Khawaja. It proves his ability to provide a serious content for the children. It seems that he is clearly interested in the children’s literature; particularly, the poetry of children, such literary genre. It sheds light on its different dimensions through which he was able to choose the non-artificial simple words. His method suited the children and their dispositions. The poetry of Khawaja does not simulate the affection and sentiment only, but it is also considered as a simulation of the child because of the indirect wisdom and sermons it contains. Additionally, it always approaches the world of childhood which is full of happiness and joy. Through his four divans which target the children he was able to employ a set of values and good morals which provide them with experiences and ideas which boost the spirit of loyalty and responsibility and upgrade their selves. This study uncovers the most significant stylistic phenomena in his poetry which he used as a way of expression for the sake of the recipient child. This is clear through his interest in conveying concepts considered by the child as familiar. The elements of the artistic imagery represented in employing the senses (such as vision, hearing, color, taste, and motion) formed a main factor and one of the prevailing characteristics in his poetry. It is because he sought to grow the imagination of the child in it. He always seeks to enrich his imagination and widen his knowledge, develop his perceptions, and deepen his awareness. Al-Khawaja managed to write for the child and reach the highest level of poetry regarding creativity in the poem, rhythm, language, and the target he seeks in his poetry.